Mathematical Literacy Analysis of Class XI Students of the PISA Model in View of Adversity Quotient (AQ) - Elisabet Putri Wardani; Herry Agus Susanto; Erika Laras Astutiningtyas (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
This study aims to describe the mathematical literacy of grade XI students of SMA Negeri 2 Karanganyar in solving the PISA problem model in terms of the Adversity Quotient. For some students, mathematical concepts can be difficult to grasp, causing frustration and disinterest with the subject. For others, external factors such as lack of resources, inadequate teaching methods, and inadequate support can contribute to poor math performance. This research is included in qualitative research. The data used were obtained from test results and interviews. The subjects of the study were carried out by grade XI students of SMA Negeri 2 Karanganyar. Data analysis procedures in this study are data collection, power reduction, data presentation, and conclusion pulling. Checking the validity of power in this study using triangulation techniques/methods. The results showed that (1) Students with climber type AQ were able to explain answers fluently and clearly, able to mention after facts, solve problems with simple strategies in solving problems. (2) Students with campers-type AQ are capable and some are unable to explain answers fluently and clearly, solving problems with simple strategies in solving problems. The types